Perencanaan Lalu Lintas Pengembangan Pelabuhan Perikanan Likupang - Pandey, Sisca; Sumarauw, Jeffry S T; Dundu, Ariestides K T (Jurnal Teknik, 2025)
The development of new land uses that become activity centers will cause traffic generation. The construction and operation of the Likupang Fishing Port in North Minahasa Regency, North Sulawesi Province has caused an increase in traffic movements. The traffic generation resulting from the development of fishing port infrastructure is classified as high traffic generation. The aim of this research is what the traffic management plan is for developing the Likupang fishing port. The research method/design begins with a background to the problem and establishing research objectives. Primary data in the form of traffic flow characteristics data consisting of volume, speed, density of traffic flow on the affected road sections. Geometric inventory data of roads, passengers getting on and off ships is calculated as a person generation calculated manually using a survey form. Secondary data in the form of population data, public transportation, road networks. The technique for collecting traffic volume data by counting the number of vehicles passing on the observation line is carried out by recording all vehicles that pass a point on the affected road section, using a hand tally counter and a survey form. The surveyor will count each type of vehicle based on its classification. The technique for collecting data on traffic flow speed is carried out manually, setting the length of the road section at 50 meters and speed calculations are carried out by 2 surveyors using the flag method. The collection of traffic flow and generation was calculated during the survey period from 06.00 – 19.00. Analysis of volume, speed, density of traffic flow and traffic flow simulation using the MKJI 1997 method. Performance of the local road section of Likupang Fishing Port, existing condition of service level B and speed of 10 km/hour. Increased traffic flow in the future will cause the service level of the Likupang Fishing Harbor collector road to decrease to service level C.Traffic management plan during the construction period a) 1 warning light warning sign. b) Installation of 2 caution signs in and out of project vehicles. c) Placement of car wash, d) guard post, e) construction material stockyard. Traffic planning at the Likupang Fishing Port when it is built and will be operated is to install - 1 caution sign, - 1 unit of entry sign, - 1 exit sign, - 1 stop sign, - 1 guard post. Traffic management planning for the construction of the Likupang Fishing Port will provide services that provide comfort to road users.